An ictogenic marker in the mesial temporal epilepsy and its temporal evolutionary features - Lu, Hongjuan; Yang, Haoran; Zhang, Wei; Liu, Xingzhou; Sun, Wei (Frontiers in Neurology, 2025)
ObjectiveTo observe and measure the morphological and temporal evolutionary features of the hypersynchronous (HYP) pattern in the mesial temporal seizure.MethodsThe HYP patterns during preictal and interictal states of 16 mesial temporal epileptic patients were analyzed. The wave components of the HYP transients were firstly observed and measured. The dynamic deformations and parameter changes of the components were further analyzed along the preictal-ictal axis. The difference of emergence rate of HYP transients and typical interictal spike during interictal periods was also compared.ResultsThe HYP transients were invariably composed of slow-wave proper, sharp wave and post-slow component among studied patients for all the 93 seizures. During preictal epoch, all of the seizures incorporated present evolutionary manner of type 1 characterized by smooth modification of HYP transients in morphology, including gradual shortening of the inter-transient interval, increase of amplitude and time duration of slow-wave proper and sharp wave, amplitude decrease of the post-slow component, as well as amplitude increases of ripple and fast ripple, and 2/3 seizures showed some more sophisticated transitional manners (type 2) following type 1, including reduction in amplitude with decrease of inter-transient intervals, superimposed or followed by the emergent low amplitude rhythmic activities, or both of them. The HYP transients and typical interictal spikes were found to mutually “repelling” each other in interictal period.ConclusionThe HYP transients showed a combinational feature and temporal evolution manners during preictal state. The emergence of HYP transients in cluster reflects the transitional trend from interictal to ictal state.SignificanceHYP should be viewed as an index of ictogenesis in the mesial temporal seizure.